PENGARUH INKLUSI KEUANGAN, EFFISIENSI KEUANGAN DAN PDB PER KAPITA TERHADAP KEBERLANJUTAN KEUANGAN - Anggraenni, Dina; Anam, A.Khoirul (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study makes an original contribution by: (1) focusing the analysis on the heterogeneous Asian context, (2) integrating three key determinants of financial stability into a single model, and (3) examining non-linear effects and differences in outcomes across country groups based on income levels. This study aims to analyze the influence of financial inclusion, financial efficiency, and GDP per capita on the sustainability of financial systems in 36 Asian countries for the period 2015–2024.Methods: This study employs a quantitative approach, utilizing panel data from the Global Financial Development Database (World Bank). The analysis was conducted using Principal Component Analysis (PCA) to form composite variables, followed by Feasible Generalized Least Squares (FGLS) regression to estimate the effects of the independent variables.Results: Financial inclusion (bank branches/ATMs) significantly impacts financial sustainability. Financial efficiency has a significant positive effect on financial sustainability. GDP per capita has a significant positive effect on financial sustainability.Conclusion and suggestion: This study produces several important findings that make significant contributions to the finance and development literature. The analysis shows that financial efficiency, particularly as measured by profitability, has a positive and significant impact on the sustainability of the financial system in the Asian region. The analysis also indicates that GDP per capita has a significant impact on financial sustainability, although with indications of a non-linear relationship. This is expected to become a financial inclusion policy that not only expands access but also maintains financial system stability. Furthermore, the finding of a non-linear relationship between GDP per capita and financial stability can be an important consideration in formulating macroeconomic policies that impact the financial sector. Keywords: Financial Inclusion, Financial Efficiency, GDP per Capita, and Financial Sustainability